Experimental Determination of the Force in the Magnetic Field of an Air Coil - Boydedayev Sobirjon Rahimjonovich; Umaraliyev Maksud Mahmudovich; Turgunov Adham Rakhmatillayevich (Peerian Journals Publishing, 2022)
This experiment measures the force exerted by an air coil on a conductor ring in a uniform magnetic field as a function of the conductor ring current I. A uniform magnetic field is produced in a long, slotted air coil, and the conducting loop is of length s. = 8 cm is inserted into the slot where the force sensor is attached. Only the horizontal part of the conductors generates the force component measured by the force sensor. Thus, the ratio between the force F and the loop current I is used to determine the magnetic flux density B
Keywords: magnetic field; ring, charge; Lorentz force; velocity